2011
DOI: 10.1002/nau.21008
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in elderly men with aging symptoms and lower urinary tract symptoms (LUTS)

Abstract: Moderate to severe ADAM and LUTS impact significantly all parameters of HRQOL and generic QoL proposed by the WHO. There was correlation between severity of LUTS and severity of the following ADAM: depression, feeling burnt out, decline of feeling of general well-being, joint and body complaints, insomnia, weakness of muscles, feeling that the peak had passed, decrease of sexual performance, and decrease of morning erections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
0
12
0
8
Order By: Relevance
“…LUTS, particularly storage symptoms, have a negative impact on patients’ HRQoL . The present analyses of data from the NEPTUNE study indicate that the FDC of solifenacin 6 mg plus TOCAS significantly improved several HRQoL parameters, vs placebo and vs TOCAS monotherapy, in men with LUTS/BPH who had moderate‐to‐severe storage symptoms and voiding symptoms.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…LUTS, particularly storage symptoms, have a negative impact on patients’ HRQoL . The present analyses of data from the NEPTUNE study indicate that the FDC of solifenacin 6 mg plus TOCAS significantly improved several HRQoL parameters, vs placebo and vs TOCAS monotherapy, in men with LUTS/BPH who had moderate‐to‐severe storage symptoms and voiding symptoms.…”
Section: Discussionmentioning
confidence: 65%
“…Other studies have shown that LUTS can negatively impact patients’ health‐related quality of life (HRQoL) . A cross‐sectional survey of 1 627 men aged 40–79 years found 51% of men with BPH reported interference with at least one daily living activity due to urinary dysfunction, compared with 28% of men without BPH .…”
Section: Introductionmentioning
confidence: 99%
“…Aging has emerged as a major global public health issue that is associated with different types of morbidity, including cancer, cardiovascular diseases, and dementia. Advancing age is also considered a high risk factor for genitourinary tract diseases, being the lower urinary tract symptoms (LUTS) secondary to benign prostate hyperplasia (BPH) the most prevalent age‐related pathological condition in men . BPH is characterized by an increase in both physical size (static component) and prostate smooth muscle tone (dynamic component).…”
Section: Introductionmentioning
confidence: 99%
“…Advancing age is also considered a high risk factor for genitourinary tract diseases, being the lower urinary tract symptoms (LUTS) secondary to benign prostate hyperplasia (BPH) the most prevalent age-related pathological condition in men. 1 BPH is characterized by an increase in both physical size (static component) and prostate smooth muscle tone (dynamic component). The BPH pathogenesis is multifactorial and may include age-related changes in the nervous system and neuroregulatory factors, such as nitric oxide (NO) and RhoA/Rho-kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the aging process, quality of life is determined by the ability to maintain autonomy, decision-making, independence and ability to perform daily tasks (Freitas, Queiroz & Sousa, 2010), its decline may contribute to the risk of chronic degenerative diseases in different populations, mostly in men over the age of 40 years (Martits & Costa, 2004). Thus, it is important to maintain adequate levels of quality of life in this population (Perchon, Pintarelli, Bezerra, Thiel & Dambros, 2011).…”
Section: Introductionmentioning
confidence: 99%